2020
DOI: 10.3390/antiox9010049
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Mechanisms of Three Natural Antioxidants on a Rat Model of Parkinson’s Disease: A Comparative Study

Abstract: We compared the neuroprotective action of three natural bio-antioxidants (AOs): ellagic acid (EA), α-lipoic acid (LA), and myrtenal (Myrt) in an experimental model of Parkinson’s disease (PD) that was induced in male Wistar rats through an intrastriatal injection of 6-hydroxydopamine (6-OHDA). The animals were divided into five groups: the sham-operated (SO) control group; striatal 6-OHDA-lesioned control group; and three groups of 6-OHDA-lesioned rats pre-treated for five days with EA, LA, and Myrt (50 mg/kg;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 96 publications
1
33
0
1
Order By: Relevance
“…Many reports confirmed the ability of LP andEAaspotentialantioxidants [ 31 ]. Finally, PDE-5 inhibitor and nanocomplex formulation with antioxidants can be the potent neuroprotective agents in the clinical treatment of DN [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many reports confirmed the ability of LP andEAaspotentialantioxidants [ 31 ]. Finally, PDE-5 inhibitor and nanocomplex formulation with antioxidants can be the potent neuroprotective agents in the clinical treatment of DN [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, EA treatment prior to MPTP administration significantly increased the GSH level and decreased the MDA level, again suggesting the antioxidant function of EA. In several studies, EA has been widely reported to exert free radical scavenging and potent antioxidant activity by scavenging ROS and restoring the activity of cellular antioxidant enzymes [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…EA treatment also improved motor function and electrophysiological performance in medial forebrain bundlelesioned rats by raising cerebral antioxidant content [177]. Other studies discovered that combined treatment with three compounds such as EA, α-lipoic acid, and myrtenal attenuated decreases in DA levels, substantially decreased lipid peroxidation levels, and restored CAT activity in 6-OHDAinduced PD rats [262].…”
Section: Neuroprotective Mechanisms Of Thymoquinone In Pdmentioning
confidence: 99%